Activity manual for adolescents - Karp, Cheryl L.; Butler, Traci L.; Bergstrom, Sage C. (Thousand Oaks : London : New Delhi : Sage Publications, 1998)
Designed to be used alongside Treatment Strategies for Abused Adolescents therapist manual, this Activity Manual has been specifically designed for adolescents working in a therapeutic setting towards healing from early physical, sexual and/or emotional trauma. Introductions to each chapter sensitively address adolescents, and the trauma resolution activities are interesting, well-planned and developmentally structured.
Keywords: Sexually abused teenagers -- Rehabilitation; Abused teenagers -- Rehabilitation; Adolescent Psychiatry